Sastra sebagai Medium Perlawanan: Telaah Sosiologi Sastra Marxis dalam Antologi Cerpen Al-Arwa?h Al-Mutamarridah karya Khalil Jibran - Insanul Hasan; Ahmad Taufik Hidayat; Ahmad Busyrowi (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2019)
This study applied Terry Eagleton's Marxist sociological literary theory to find the relations of production, economic structure and social behavior in society called infrastructure which has the essential function to legitimize social classes. Thus, the concept of ideas and consciousness, which also called superstructures, are the ideas of the authority. This research found forms of social relations that cause class struggle. The alienation of the people as a group of the proletariat was the result of oppression by the Shaykh Abbas as a bourgeoisie from the ownership of the entire village's wealth. Khalil, as Marxist hegemony, tried to build awareness of the people who have been exploited to fight to live without oppression.